Difference in the Effect of Giving Neck Stabilization Exercise with Stretching on Improvement of Neck Functional Ability in Non-Specific Neck Pain - Almas Khonsa Dekamelania; Nur Basuki; Yulianto Wahyono (Indonesian Journal of Medicine, 2023)
Background:  Tailor workers when working with a bowed position and a long static position, the muscles will contract excessively resulting in spasms and pain that causes non-specific neck pain which will interfere with the functional ability of the neck. Neck stabilization exercises and stretching can be exercises to improve neck functional ability in non-specific neck pain. This study aims to determine the difference in the effect of neck stabilization exercise and stretching on increasing the functional ability of the neck in non-specific neck pain. Subjects and Method:  This study is a randomized controlled trial using a two-group pretest and post-test design conducted at sevinta convection and padi emas from November to December 2023. A total of 24 subjects were selected by random sampling and randomly allocated into 2 groups. Group 1 was given neck stabilization exercise and group 2 was given stretching. The dependent variable is neck functional ability in non-specific neck pain and the independent variables are neck stabilization exercise and stretching. The measuring instrument used is the neck disability index to measure neck functional ability. Data analysis using independent sample t-test. Results:  The results after the intervention obtained neck functional ability in non-specific neck pain increased in both groups. There is a statistically significant difference in neck stabilization exercise (Mean = 4.00; SD = 2.21) and stretching (Mean = 6.83; SD = 2.79), and it was statistically significant (p = 0.012). Conclusion:  There is a significant difference in the effect of neck stabilization exercise and stretching on improving neck functional ability in non-specific neck pain. Neck stabilization exercise is more influential than stretching on improving neck functional ability in non-specific neck pain. Keywords:  neck stabilization exercise, stretching, neck disability index. Correspondence:  Yulianto Wahyono, School of Health Polytechnics Ministry of Health Surakarta. Jl. Adi Sumarmo, Tohudan, Colomadu, Karanganyar 57173, Central Java, Indonesia. Email: yulianto2wahyono@gmail.com. Mobile: 085742017903. Indonesian Journal of Medicine (2023), 08(03): 258-265